(untitled) (World Bulletin of Social Sciences, 2025)
This article analyzes the transition of journalism to the online system and its impact on society through its activities on social networks. It explores new methods of information dissemination, the problem of fake news, and issues related to media literacy. The article reconsiders the role and responsibility of journalism in the modern media environment. Scientifically grounded suggestions and conclusions are presented.